2008
DOI: 10.1007/s11666-007-9150-4
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature Oxidation Behavior and Surface Roughness Evolution of VPS NiCrAlY Coating

Abstract: In this work, as a background to the development of high temperature environmental protection coating technology, the structural transformation of vacuum-plasma sprayed NiCrAlY coating has been studied, including the oxidation behavior, elastic modulus, microhardness, and surface roughness. Coating was oxidized isothermally at a 1,273 K for different time periods up to 1,000 h in order to form the oxide scale layer. The results showed that the oxide scale and weight gain increased proportional to the exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…This agrees with other work reported in the literature [12,19,58]. It has also been reported that surface roughness can affect the yttrium distribution by forming yttrium aluminides in concave regions of the coating [59], but this has not been observed in this study.…”
Section: Surface Roughnesssupporting
confidence: 92%
“…This agrees with other work reported in the literature [12,19,58]. It has also been reported that surface roughness can affect the yttrium distribution by forming yttrium aluminides in concave regions of the coating [59], but this has not been observed in this study.…”
Section: Surface Roughnesssupporting
confidence: 92%
“…low pressure plasma spraying (LPPS), vacuum plasma spraying (VPS) and, more recently, high velocity oxy-fuel (HVOF) thermal spraying [28][29][30][31][32][33][34][35][36][37][38][39][40]. It is generally recognised that the rate of Al loss and the β-phase depletion behaviour is closely related to the oxide growth kinetics at the oxide/coating interface.…”
Section: Introductionmentioning
confidence: 99%
“…NiCrAlY, CoNiCrAlY and NiCoCrAlY coatings have been obtained by various techniques such as vacuum plasma spray (VPS) [15][16][17][18][19], electron beam physical vapor deposition (EB-PVD) [20], air plasma spray (APS) [21][22][23], high frequency pulse detonation (HFPD) [24] and high velocity oxygen fuel (HVOF) [10,12,16,19,21,[25][26][27][28][29][30][31]. In recent years, HVOF sprayed coatings has been particularly interesting because they possess high density, strong substrate adhesion and are able to maintain nano-scale structure after spraying [32].…”
Section: Introductionmentioning
confidence: 99%